Study of various synthesis parameters on the size and loading of polymeric microspheres loaded with antibiotic drug for treatment of osteomyelitis - Huang, Xiaojun. (2011)
Osteomyelitis is a bacterial infection of the bone which is commonly found in open fracture treatments and post-surgery of orthopedic implant. It can result in serious health complications such as amputation and even life threatening conditions if proper treatment was not given. Conventional treatments such as the use of antibiotic therapy can lead to bacterial resistance to drugs, systemic toxicity and discomfort in patients. Targeted drug delivery system using biodegradable microspheres offers a better alternative for long-term administration of drugs in treating osteomyelitis. In this project, poly(lactic-co-glycolic acid) (PLGA) microspheres loaded with hydrophilic drug, gentamicin (GEN) were synthesized using water-in-oil-in-water (w/o/w) double emulsion technique. The surfactants used were poly(ethylene-alt-maleic anhydride) (PEMA) and poly(vinyl alcohol) (PVA). Since the drug carrier will require a one-time injection to administer the drug to site of infection, both the size and drug loading of microspheres are important in ensuring successful treatment. Hence, various synthesis parameters affecting the particle size and drug loading were investigated to achieve the desired results. Scanning electron microscopy (SEM) was used to study the size of the microspheres. Drug loading and zeta potential were determined by using UV-Visible Spectrophotometer and Zetasizer Nano respectively. GEN-loaded PLGA microspheres were then coated with calcium phosphate (CaP) which resembles the mineral phase of natural bone to make it bioactive. Energy dispersive x-rays spectroscopy (EDX) was used to detect the presence of CaP.